Data Analytics: Why Data Normalization - K. Dhana Sree, Dr.; C. Shoba Bindu, Dr. (International Journal of Engineering and Technology, 2018)
The two maestros Artificial Intelligence and Machine learning are ruling the data filled world with good analytics. Many of these domain skills are used in the industry to analyze and interpret the data beyond what it actually is. Supporting the known saying find the horse before the cart is ready is what it mean to normalize the data before getting it analyzed. This article focus on what normalization actually is, why normalization is needed before data analysis and how data normalization is done.Â Â